2009
DOI: 10.1007/s11103-009-9578-7
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of GhPEL gene, encoding a pectate lyase, in cell wall loosening by depolymerization of the de-esterified pectin during fiber elongation in cotton

Abstract: Cotton fiber elongation, largely achieved by cell wall loosening, is an important stage during cotton fiber development. In this present research, a fiber preferential cDNA encoding a pectate lyase (PEL) which could exclusively degrade the de-esterified pectin was isolated from a cotton (Gossypium hirsutum) fiber cDNA library. Subsequently, the corresponding PEL genes were isolated from four different cotton species and characterized. In vitro enzyme assays indicated that GhPEL really exhibited cleavage-activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…In cotton fibers and trichomes, there exists a positive correlation between pectic sheath and elongation [79] and recent studies by [80] have established that pectic polysaccharides and xyloglucan containing uronic acids were the major polysaccharides extracted during elongation. Hence, our results are in agreement with various studies which state that pectin biosynthesis promotes fiber elongation [81] and that the degree of esterification is a key factor in controlling the elongation [38], [82]. The correlation between length and HG was not detected in the sPLS analysis most likely because the stronger (negative) correlation of HG with micronaire.…”
Section: Discussionsupporting
confidence: 92%
“…In cotton fibers and trichomes, there exists a positive correlation between pectic sheath and elongation [79] and recent studies by [80] have established that pectic polysaccharides and xyloglucan containing uronic acids were the major polysaccharides extracted during elongation. Hence, our results are in agreement with various studies which state that pectin biosynthesis promotes fiber elongation [81] and that the degree of esterification is a key factor in controlling the elongation [38], [82]. The correlation between length and HG was not detected in the sPLS analysis most likely because the stronger (negative) correlation of HG with micronaire.…”
Section: Discussionsupporting
confidence: 92%
“…For pathogen defense, the accumulation of pectin increases hydrogen bonding in the extracellular matrix, resulting in decreased nutrient availability to the pathogen (Vogel et al, 2002). The decrease of de-esterified pectin in cotton fiber can promote its elongation (Wang et al, 2010). Our study also demonstrates that the mutant phenotype of del1 depends on the alteration of cell wall composition and structure.…”
Section: Possible Molecular Mechanism Of Del1 Responsible For the Mutmentioning
confidence: 58%
“…PELs have been extensively studied in plant pathogenic bacteria such as Erwinia chrysanthemi, which causes soft-rot diseases (Barras et al, 1994). In plants, multiple functions have been identified for PEL, and there is some suggestion that it is involved in pollen, anthers, pistils, and developing tracheary elements (Wing et al, 1990;Rogers et al, 1992;Wu et al, 1996;Kulikauskas and McCormick, 1997;Domingo et al, 1998;Milioni et al, 2001), fruit softening and ripening (Dominguez-Puigjaner et al, 1997;Medina-Escobar et al, 1997;Nunan et al, 2001;Pua et al, 2001), lateral root emergence (Laskowski et al, 2006), cotton fiber elongation (Wang et al, 2010), leaf senescence (Wu et al, 2013), and susceptibility to plant pathogens (Vogel et al, 2002). It has also been shown to be expressed in a wide range of tissues (Palusa et al, 2007;Sun and van Nocker, 2010).…”
mentioning
confidence: 99%
“…Transgenic modification of cell wall structural proteins and enzymes has also been carried out. Li et al (2009) reported that suppression of fasciclin-like arabinogalactan proteins by expression of a GhABP4-targeted RNAi transgene inhibited fiber elongation resulting in shorter mature fibers, while antisense suppression of the pectate lyase gene GhPEL also reduced fiber elongation (Wang et al 2010a).…”
Section: Discussionmentioning
confidence: 99%